Fenómeno socio jurídico de la violencia intrafamiliar por los progenitores hacia adolescentes como un factor que incide problemas de adicción al alcohol, sustancias sujetas a fiscalización y suicidio - Benítez Maza, María Nilda (2022)
Domestic violence is one of the main causes for the consumption of alcohol and controlled substances in adolescents in our country. This situation presents a serious side effect that is suicide, causing psychological impacts to their relatives or possible disintegration in the worst case. As a result of this problem, it has been considered important to develop this thesis project titled: SOCIO-LEGAL PHENOMENON OF DOMESTIC VIOLENCE BY PARENTS TOWARDS ADOLESCENTS AS A FACTOR THAT AFFECTS PROBLEMS OF ADDICTION TO ALCOHOL, SUBSTANCES SUBJECT TO CONTROL AND SUICIDES. One of the points that will be analyzed is how domestic violence affects adolescents and the irreversible sequelae that affect their vital development and family environment, regardless of socioeconomic status, age or gender. To this end, the following objectives have been contemplated: 1. To carry out a socio-legal analysis regarding domestic violence, its incidence in children and adolescents, repercussions, problems of alcohol addiction, substances subject to control and suicide. 2. To expose the most common types of violence in our society, and their consequences 3. To propose an additional paragraph in Article 62 of the Organic Law to prevent and eradicate domestic violence, which establishes economic reparation in addition to those established in the COIP, and psychological treatment of the victim by the aggressor. The methods used will allow to analyze, compare and deduce the problems around the issue raised. In addition, it was considered necessary to conduct surveys and interviews and subsequently apply them to legal professionals. The results that will be obtained will serve as support to support the proposal of an additional paragraph in Article 62 of the Integral Organic Law to prevent and eradicate violence against women, which establishes economic reparation in addition to those established in the COIP and psychological treatment of the victim by the aggressor. The hypothesis is as follows: Domestic violence by parents towards children and adolescents is an obvious problem today, and its incidence in adolescents that leads to embark on the world of addictions to alcohol and substances subject to control. Within the legal framework, we proceeded to interpret and analyze norms related to the problem among them: Constitution of the Republic of Ecuador, International instruments, Inter-American Convention on Human Rights (Pact of San José de Costa Rica), Universal Declaration of Human Rights, Organic Code Comprehensive Criminal Code, Children and Adolescents Code, Civil Code, Comprehensive Organic Law to 5 Prevent and Eradicate Violence against Women; in comparative law, similarities are made with the Constitution of Brazil and the Organic Integral Penal Code of Colombia. The most common types of domestic violence and their effects will be described, as a reference to know a little more about this type of social problems. It will address the lack of knowledge of the laws on the part of the victims and the fear of reporting for fear of reprisals. In addition, cases that have occurred in our society will be presented to analyze them, know how the competent authorities have acted and the completion